Formulasi Sediaan Face Mist Halal Ekstrak Air Putik Bunga Saffron (Crocus Sativus L.) - Azmi Rahmadani; Priyagustin, Vira Risti; Roffada, Rizal (Sultan Agung Islamic University of Semarang, 2023)
Background: Face mist is a freshener that serves to refresh the skin. Saffron (Crocus sativus L.) was chosen as the active ingredient because it contains crocin, pirocrocin, and safranal. The phenolic and carotenoid compounds present in saffron are the most important sources of antioxidant activity. This study aims to formulate face mist halal of saffron flower extract. Methods: Saffron were extracted by maceration method using aquadest. Face mist with different extract concentration (F1: 0,7%, F2: 0,8%, and F3: 1%) was made with some additional additives. Identification of product halalness is studied based on list issued by Indonesian Ulama Council. Several characteristic tests have been carried out such as organoleptic test, pH, spray spreadability test, spray condition test, and dry time test. Results: In general, the results of halal identification found that all materials used in this study were halal. Physical characteristics test show that F1, F2, and F3 meet the requirements of good face mist where F3 has better dry time. Conclusion: Formulation 3 (F3) was the best formulation found in this study with the best organoleptic conditions, pH, spray power, dispersion, and dry time.